DASAR-DASAR PEMFORMATAN DATA KESEHATAN DALAM MICROSOFT WORD - Kezia Sumanti; Chelcya Gosal; Keren Sumanti; Wiglly Kasenda; Mutiara Zeke; Karen Sarta; Florensia Tururadja; Ildiva Lemo; Alexsandra Munthe; Prisilia Moningka (STIKES Columbia Asia Medan, 2024)
Microsoft Word is an application that is already familiar to users. Microsoft is widely used to creted documents and edit documents .Microsoft Word is an application made by a company that is the name as the windows computer operating system. Microsoft Word ia a program or word processing application, namely software, which has the funtion of creating writing documentsin various formats, such as papers, journal, reports amd so on. Microsoft Word is an application thet is ofthen referrend to as Ms Word or Word which has a main design called WYSIWYG ( What you see is what you get). with this design Microsoft is able to display words written by its users and will appear as typed by the user, besides this design also has features such as copy, or copy paste. In its development, Microsoft can not only be used to procces words, but can also insert images, graphs and tables . in addition, its use can alsocreate text in various formants, namely italicized, bold, colored and underline words.In this article, we will discuss the basic formatting that can be used by those using Microsoft Word. This research also aims to provide an understanding of hoe to use basic Microsoft Word formatting and to make it easier for users, especially students.